First Report of Charcoal Rot on Soybean Caused by Macrophomina phaseolina in Manitoba, Canada - Kim, Yong Min (Plant disease, 2023)
Macrophomina phaseolina (Tassi) Goid. is a soilborne necrotrophic fungal pathogen causing charcoal rot on approximately 500 plant species worldwide (Mengistu et al. 2015). Charcoal rot occurs in eastern Canada and many regions of the USA, causing substantial yield losses in soybean [Glycine max (L.) Merr.] (Allen et al. 2017; Bradley et al. 2021; Wrather et al. 2001). However, it has not been reported in soybean in western Canada. Manitoba is the second largest soybean producer in Canada, comprising 31% of total seeded areas with 2.29 M acres in 2017 (Statistics Canada 2022). Still, soybean is a relatively new crop to Manitoba and annual surveys of soybean root diseases began in 2012. In August 2020, randomly selected soybean fields were surveyed for root diseases at 63 different locations in south-central and southwest Manitoba. A total of thirty diseased plants were sampled in a zigzag pattern at three random sites in each field and all samples were brought to the laboratory and rated for disease severity. All plants showed symptoms of root rot, and some samples exhibited wilting with yellowing-brown leaves attached to the stems by the petioles; when the taproot was sectioned longitudinally, black streaking could be observed. In the laboratory, 600 roots from 40 selected fields were processed for pathogen isolation and identification. A 1 cm section from each root was surface-sterilized in a 95% EtOH:5.25% NaOCl solution for 30 sec, rinsed in sterile water for 60 sec, and air-dried on sterilized filter paper in a laminar flow hood. Root tissues with two replicates were placed on potato dextrose agar (PDA) plates amended with streptomycin sulfate (2 mg/mL) and incubated at room temperature. Black microsclerotia were observed in cultures from three different fields and three individual fungal isolates were obtained from each field through isolation of a single microsclerotium and subsequent hyphal tip transfer. The mycelia were initially hyaline and turned gray to dark brown or black, forming numerous microsclerotia ranging in size from 13 to 61 µm long and 12 to 32 µm wide, based on measurements of approximately 100 microsclerotia per isolate using a Zeiss Axio Imager A2 microscope equipped with an AxioCam HRc (Carl Zeiss, Jena, Germany) and AxioVision software. The color of the microsclerotia was jet black and the shape was round to oblong or irregular, as described by Mengistu et al. (2015). Based on morphological characteristics and microscopic examination, three fungal isolates were identified as M. phaseolina (Mengistu et al. 2015). For molecular identification, genomic DNA was extracted from 10 to 14-day old mycelia and microsclerotia of each isolate using a ZymoBIOMICS™ DNA Miniprep Kit (Zymo Research Corp., Irvine, CA, USA) according to the manufacturer's instructions. The internal transcribed spacer (ITS) region, translation elongation factor-1α (TEF-1α), and calmodulin (CAL) genes were amplified using the primer sets ITS1/ITS4 (White et al. 1990), MpTefF/MpTefR, and MpCalF/MpCalR (Santos et al. 2020), respectively, according to the original reaction conditions. Subsequently, PCR products were sequenced at Eurofins Genomics (Louisville, KY, USA). BLASTn analysis in GenBank showed that the nucleotide sequences of these regions of the three isolates (NSRR20-MB-24, NSRR20-MB-34, and NSRR20-MB-40) matched multiple isolates of M. phaseolina with 100% query cover and 100% identity. Sequences were deposited in GenBank for the ITS (OK127887, OK142725, OK128266), TEF-1α (OR363103, OR363104, OR363105), and CAL (OR357627, OR357628, OR357629) regions. In addition, the ITS and TEF-1α sequences of the three novel isolates were further aligned with multiple previously reported isolates of M. phaseolina, M. pseudophaseolina, and M. euphorbiicola (Chen et al. 2013; Machado et al. 2019; Sarr et al. 2014) using Muscle and trimmed (Edgar 2004). Alignments were concatenated to generate a maximum likelihood tree. Once concatenated, sequences were re-aligned. The obtained alignments were employed to construct a phylogenetic tree using the max likelihood method and Tamura-Nei model (Tamura and Nei 1993) with 10,000 bootstrap replicates using MEGA 11 (Tamura et al. 2021). The ITS and TEF-1α analysis indicated that the isolates were grouped in three differentiated clades (Figure 1). Macrophomina phaseolina isolates clustered in the same clade at 98% similarity, with the three novel soybean isolates NSRR20-MB-24, NSRR20-MB-34, and NSRR20-MB-40 grouped closely in the cluster at 98% similarity and identified as M. phaseolina. In contrast, isolates of M. euphorbiicola formed another clade at 87% similarity and M. pseudophaseolina isolates grouped in a clade at 99%. The pathogenicity of the three isolates was evaluated under controlled conditions. Given that no information on charcoal rot resistance in soybean has been reported in Canada, one of the commonly grown varieties in Manitoba, "TH 32004", was selected for the pathogenicity test. Surface-sterilized soybean seeds, which had been pre-germinated for three days, were sown in a sterilized soilless growing mix (Sunshine #5) together with 5 g (approx. 1 × 105 microsclerotia) of macerated 10 to 14-day old inoculum grown on PDA-streptomycin agar medium at room temperature and applied using an inoculum layering technique. For the non-inoculated control, macerated PDA-streptomycin agar without mycelia was used. Twenty plants per treatment were maintained in a walk-in plant growth chamber with a 16 h photoperiod at 25/20 °C ± 1 °C (day/night) and 50% relative humidity. Plants were watered weekly but were subjected to water stress. Symptoms of charcoal rot were observed in the root systems of all inoculated soybean plants after 28 days, while no symptoms were observed in the control plants (Figure S1). There was production of microsclerotia on the roots inoculated with each isolate (data not shown). Three isolates of M. phaseolina were re-isolated from the inoculated plants and found to be identical to the inoculated isolates with respect to morphological characteristics in culture, as well as with respect to the ITS, TEF-1α and CAL DNA sequences. For each isolate and non-inoculated control, five seeds of 'TH 32004' were seeded per pot, and four pots were used for the inoculated and control treatments. The experiment was repeated twice in a randomized complete block design with similar results, fulfilling Koch's postulates. To our knowledge, this is the first report of charcoal rot caused by M. phaseolina on soybean in Manitoba, Canada